Letter - Fernández-Shaw, Daniel
029-0178-001 1258 AGREGADO COMERCIAL A LA EMBAJADA DE ESPAÑA 21, CAVENDISH SQUARE, LONDON, W. 1 . TELEFONO. LANGHAM 3671 TELEGRAMS "OFCOMES" LONDON. Your Ref. HVT/EK/656. 10th April 1937. H.V. Tewson Esq., Trades Union Congress, Transport House, Smith Square, S.W.1. Dear Mr. Tewson, I wish to confirm telephonic conversation yesterday evening, informing you that the steamer which will take the food you wish to send to Spain will be the s.s. "BACKWORTH" which will sail from Immingham on the 15th instant for Bilbao. I am taking advantage of this opportunity of expressing my gratitude for the help you are rendering the Spanish people at this unfortunate time, and remain, Yours faithfully, The Commercial Attaché to the Spanish Embassy. Daniel Fernandez-Shaw 292/946/29/178